Horizon of Expectation of Mandarin Students Towards the Novel Huo Zhe (æ´»ç€): Literary Reception Approach - Erwani, Intan; Julina (Talenta Publisher, 2024)
This study discusses the horizon of expectations of the students in the novel HuÃ³zhe (æ´»ç€) by Yu Hua. This research aims to measure the horizon of expectations that readers have regarding the ideas conveyed by the novel Huo Zhe (æ´»ç€), so it is hoped that this can contribute to the development of literary reception theory. The theory used is the literary reception theory which focuses on exploring the form of a horizon of expectation, so that the presence of a literary work can be accepted in society. The methodology used is qualitative descriptive method as a basis for determining variables, problem formulation, data collection techniques, data classification and data analysis. The research informants were 35 students majoring in the Mandarin Language from 6th and 8th semesters who had taken the concentration in literature. Informants will be asked to read Yu Hua's novel HuÃ³zhe (æ´»ç€) and provide their responses through a questionnaire. The results of this study indicate that the novel HuÃ³zhe (æ´»ç€) fulfils the 3 criteria carried in the Jauss theory, namely the values depicted in the text, the knowledge and experience of the readers, and the conflict between fiction and reality. Thus, it can be concluded that the reading informants from the 6th and 8th-semester students majoring in Chinese accept the novel HuÃ³zhe (æ´»ç€) positively, The results of acceptance positively influence new views that are built into the reader's horizon of expectations in interpreting the meaning of the ideas conveyed by the novel.